Lay Theories About Whether Emotion Helps or Hinders: Assessment and Effects on Emotional Acceptance and Recovery From Distress - Karnaze, Melissa M.; Levine, Linda J. (Frontiers in Psychology, 2020)
This investigation examined how people’s beliefs about the functionality of emotion shape their emotional response and regulatory strategies when encountering distressing events. In Study 1, we present data supporting the reliability and validity of an 8-item instrument, the Help and Hinder Theories about Emotion Measure (HHTEM), designed to assess an individual’s beliefs about the functionality of emotion. Participants who more strongly endorsed a Help Theory reported greater wellbeing, emotional acceptance, and use of reappraisal to regulate emotion. Participants who more strongly endorsed a Hinder Theory reported less wellbeing and more expressive suppression and substance use. In Study 2, we demonstrate that encouraging participants to view emotion as helpful affected their physiological and regulatory response to a distressing event. Participants in the Help Theory condition showed greater physiological reactivity (SCL) during a distressing film than control participants but were more accepting of their emotional response. Shortly after the film, SCL decreased for participants in the Help Theory condition. Compared to control participants, they engaged in less suppression and reported less lingering effect of the film on their mood. Together, these studies suggest that people’s theories about the functionality of emotion influence their reactivity, the strategies they adopt to regulate emotion, and their ability to rebound after distressing events.